Controlled removal of amorphous Se capping layer from a topological insulator - Virwani, K; Harrison, SE; Pushp, A; Topuria, T; Delenia, E; Rice, P; Kellock, A; Collins-McIntyre, L; Harris, J; Hesjedal, T; Parkin, S (2014)
© 2014 AIP Publishing LLC. We report on the controlled removal of an amorphous Se capping layer from Bi2Te3 and Bi2Se3 topological insulators. We show that the Se coalesces into micron-sized islands before desorbing from the surface at a temperature of ∼150°C. In situ Auger Electron Spectroscopy reveals that Se replaces a significant fraction of the Te near the top surface of the Bi2Te3. Rutherford Backscattering Spectrometry and Transmission Electron Microscopy show that after heating, Se has been incorporated in the Bi2Te3 lattice down to ∼7 nm from its top surface while remaining iso-structural.